RETRACTED: The attitude of future ecologists to the formation of soft skills in the context of achieving sustainable development goals - Ermakov Dmitry; Ermakov Alexander (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001